2022
DOI: 10.1038/s41387-022-00187-2
|View full text |Cite
|
Sign up to set email alerts
|

Growth differentiation factor 15 (GDF15) is associated with non-alcoholic fatty liver disease (NAFLD) in youth with overweight or obesity

Abstract: Objective Growth differentiation factor 15 (GDF15) has been associated with food intake and weight regulation in response to metabolic stress. In animal models, it has been noted that it may play a role in the progression of non-alcoholic fatty liver disease (NAFLD), the leading cause of chronic liver disease in children. Design In the current study, we explored the association of circulating plasma concentrations of GDF15 with NAFLD in youth with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
0
10
1
Order By: Relevance
“…We [ 33 ] and others [ [34] , [35] , [36] ] have shown that activation of the ISR (via nutritional, genetic or pharmacological stressors) is associated with increased expression of growth differentiation factor 15 (GDF15) and fibroblast growth factor 21 (FGF21). Plasma levels of both FGF21 [ [37] , [38] , [39] , [40] , [41] ] and GDF15 [ [42] , [43] , [44] ] are known to be increased in obese humans and rodents as well as in other metabolic disease states such as insulin resistance [ 45 , 46 ], NAFLD [ [47] , [48] , [49] , [50] , [51] , [52] ] and mitochondrial disease [ 53 , 54 ]. Both stress-induced cytokines, GDF15 and FGF21, have attracted considerable interest as potential therapies for obesity and its associated metabolic disease [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…We [ 33 ] and others [ [34] , [35] , [36] ] have shown that activation of the ISR (via nutritional, genetic or pharmacological stressors) is associated with increased expression of growth differentiation factor 15 (GDF15) and fibroblast growth factor 21 (FGF21). Plasma levels of both FGF21 [ [37] , [38] , [39] , [40] , [41] ] and GDF15 [ [42] , [43] , [44] ] are known to be increased in obese humans and rodents as well as in other metabolic disease states such as insulin resistance [ 45 , 46 ], NAFLD [ [47] , [48] , [49] , [50] , [51] , [52] ] and mitochondrial disease [ 53 , 54 ]. Both stress-induced cytokines, GDF15 and FGF21, have attracted considerable interest as potential therapies for obesity and its associated metabolic disease [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…We (Patel et al, 2019) and others (Chung et al, 2017; Dong et al, 2015; Laeger et al, 2014) have shown that activation of the ISR (via nutritional, genetic or pharmacological stressors) is associated with increased expression of growth differentiation factor 15 (GDF15) and fibroblast growth factor 21 (FGF21). Plasma levels of both FGF21 (Gómez-Ambrosi et al, 2017; Kharitonenkov et al, 2005; Kralisch et al, 2013; Reinehr et al, 2012; Zhang et al, 2008) and GDF15 (Carballo-Casla et al, 2021; Vila et al, 2011; Xiong et al, 2017) are known to be increased in obese humans and rodents as well as in other metabolic disease states such as insulin resistance (Chavez et al, 2009; Kempf et al, 2012), NAFLD (Bilson et al, 2021; Dushay et al, 2010; Galuppo et al, 2022; Kim et al, 2018; Rusli et al, 2016; Tucker et al, 2019) and mitochondrial disease (Poulsen et al, 2020; Suomalainen et al, 2011). Both stress-induced cytokines, GDF15 and FGF21, have attracted considerable interest as potential therapies for obesity and its associated metabolic disease (Keipert and Ost, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A meta‐analysis of 51 studies involving 36 074 patients and 47 052 controls showed that elevated levels of CRP, IL‐1β, IL‐6, TNF‐α, and intercellular cell adhesion molecule‐1 were significantly associated with increased risk of NAFLD 49 . Plasma GDF15 concentration was measured in 175 overweight/obese adolescents and showed that GDF15 changed with changes in intrahepatic fat content 50 . Ectodysplasin A, a liver secreted protein, is elevated in NAFL and NASH and is associated with progression of steatosis and fibrosis 51 .…”
Section: Discussionmentioning
confidence: 99%
“…49 Plasma GDF15 concentration was measured in 175 overweight/obese adolescents and showed that GDF15 changed with changes in intrahepatic fat content. 50 Ectodysplasin A, a liver secreted protein, is elevated in NAFL and NASH and is associated with progression of steatosis and fibrosis. 51 Moreover, a Korean study involving 2735 participants showed an inverse association between adiponectin and the prevalence of NAFLD and could even serve as a novel biomarker for NAFLD.…”
Section: (B) Analysis Of Correlation Between Il2rb (Interleukin-2 Rec...mentioning
confidence: 99%